(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Pleomorphic adenoma, the most common benign neoplasm of salivary gland tumor, consists of epithelial (ductal and nonductal) and mesenchymal components. Its morphologic complexity results from differentiation of tumor cells into fibrous, hyalinized, myxoid, chondroid and osseous areas. The diagnosis is made by the clinical and histopathological examination. The treatment of pleomorphic adenoma is surgical excision. Malignant transformation, though rare, has been reported.